Neutral merocyanine dyes: for in vivo NIR fluorescence imaging of amyloid-β plaques. Issue 71 (22nd August 2017) - Yan, Jin-wu; Zhu, Jia-ying; Zhou, Kai-xiang; Wang, Jin-sheng; Tan, Hui-ya; Xu, Zhong-yong; Chen, Shuo-bin; Lu, Yu-ting; Cui, Meng-chao; Zhang, Lei
Abstract : Two neutral merocyanine-based near-infrared fluorescent probes were for the first time developed through rational engineering of the classical cationic cyanine scaffoldIR-780 for in vivo imaging of amyloid-β plaques. Abstract : Two neutral merocyanine-based near-infrared fluorescent probes were for the first time developed through rational engineering of the classical cationic cyanine scaffoldIR-780 for in vivo imaging of amyloid-β plaques. In vivo NIRF imaging revealed that the probe could penetrate the blood–brain barrier and efficiently differentiate the living transgenic and wild-type mice.